(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The coastal psammophytic vegetation of Ukraine comprises coenoses which belong to 47 assosiatoins, 7 unions, 4 orders and 4 classes: Cakiletea maritimae, Ammophiletea, Festucetea vaginatae and Nerio-Tamaricetea, all of high rarity. The class Cakiletea maritimae includes four associations which belong to the first conservation category. In the class Ammophiletea three associations fall into the first conservation category and three - to the third one. The majority of coastal plant communities of class Festucetea vaginatae belong to the first (8 associations) and third (2 associations) conservation categories. Two of four associations of Nerio-Tamaricetea have the highest synsozological status, and another association has the fourth conservation category. Regionally, the highest degree of rarity has the coastal psammophytic vegetation of the Azov sand banks. The Dzharylgach and Tendra islands, Kinburn sand bank and seashore territories of Kiliyan Arm of Danube are rich on rare associations. Coastal regions of the Crimea, Syvash and North-Western Black Sea have comparatively less rare plant communities.